Determining Optimal Outcome Measures in a Trial Investigating No Routine Gastric Residual Volume Measurement in Critically Ill Children. Issue 1 (6th March 2020) - Tume, Lyvonne N.; Arch, Barbara; Woolfall, Kerry; Roper, Louise; Deja, Elizabeth; Jones, Ashley P.; Latten, Lynne; Eccleson, Helen; Hickey, Helen; Pathan, Nazima; Preston, Jenny; Beissel, Anne; et al.
Abstract: Background: Choosing trial outcome measures is important. When outcomes are not clinically relevant or important to parents/patients, trial evidence is less likely to be implemented into practice. This study aimed to determine optimal outcome measures for a trial of no routine gastric residual volume (GRV) measurement in critically ill children. Methods: A mixed‐methods approach was used: a focused literature review, parent and clinician interviews, a modified 2‐round Delphi, and a stakeholder consensus meeting. Results: The review generated 13 outcomes. Fourteen pediatric intensive care unit (PICU) parents proposed 3 additional outcomes; these 16 were then rated by 28 clinicians in Delphi round 1. Six further outcomes were proposed, and 22 outcomes were rated in the second round. No items were voted "consensus out." The 18 "no‐consensus" items were voted in a face‐to‐face meeting by 30 participants. The final 12 outcome measures were time to reach energy targets, ventilator‐associated pneumonia, vomiting, time enteral feeds withheld per 24 hours, necrotizing enterocolitis, length of invasive ventilation, PICU length of stay, mortality, change in weight and markers of feed intolerance (parenteral nutrition administered), feed formula altered, and change to postpyloric feeds all secondary to feed intolerance. Conclusion: We have identified 12 outcomes for a trial of no GRV measurement through a multistage process, seeking views of parents and clinicians.